Queering spirituality and community in the deep South - Strunk, Kamden K. (Emerald Publishing Limited : Information Age Publishing Inc., 2019)
In this volume, authors explore the interconnected issues of spirituality and community as they relate to queer issues in the Deep South. The book begins with explorations of queer spiritualities and LGBTQ people in religious settings. Next, authors investigate and document the rise of the religious right political movement in the South. Finally, the authors of this text document community life for LGBTQ people in the Deep South, including efforts to create affirming queer spaces inside otherwise hostile locales.Through the chapters in this text, the peculiarities of spirituality and community life for LGBTQ people in the Deep South are explored. However, this volume also points to trends, themes, and dynamics at work in the Deep South that are also implicated in the queer experience in other parts of the U.S. The authors of this text push readers to think deeply about these issues, probe the limits of queer potentialities in Southern religious and community contexts, and clearly point to the interweaving of Christian religiousness, communities of practice, the operation of white supremacist heteropatriarchy in oppression of LGBTQ people, and the possibilities of affirming spiritual and community praxis.
Keywords: Sexual minority community -- Southern States.; Sexual minorities -- Relgious life -- Southern States.; Homosexuality -- Social aspects -- Southern States.; Homosexuality -- Religious aspects -- Christianity.; Spirituality -- Southern States.; Social Science -- LGBTQ+ Studies -- General.; LGBTQ+ Studies, topics.; Relating to LGBTQ+ people.; elektronické knihy; electronic books